Effect of sodium alginate on the properties of microbial repair materials and its repair effect on mortar crack - Rong, Hui; Hu, Kaiyue; Ma, Guowei; Zheng, Xinguo (Frontiers in Materials, 2022)
In recent years, microbial repair materials have received widespread attention for their advantages such as stable products and good compatibility with cementitious materials. However, the current construction process of microbial repair materials is mainly by immersion, which limits the more widespread application. Therefore, this paper proposed a coating construction process with sodium alginate as the carrier. The effects of sodium alginate concentration and dosing on the basic properties of microbial repair materials (CaCO3 content, mechanical properties, water absorption ratio and heating shrinkage rate) and their effects on mortar repair effects (macroscopic morphology and surface water absorption ratio) were investigated. The repair effects were further verified by combining thermogravimetric analysis of repair products and scanning electron microscopy. The results showed that (1) the microbial repair material had better basic properties when sodium alginate solution with a mass concentration of 1.5% was used, and its solution-to-bacterial solution volume ratio was 8:2, 7:3 and 6:4; (2) using the coating technique, the microorganisms were fixed in the cracks on the mortar surface by using sodium alginate as the carrier. Only 2 times of repair could generate a mixture of calcium alginate and calcium carbonate crystals in the cracks by close adhesion. The repair effect was remarkable, with a 67% reduction in surface water absorption rate compared to before the repair.